Facile synthesis of N-acyl 2-aminobenzothiazoles by NHC-catalyzed direct oxidative amidation of aldehydes - Premaletha, Sethulekshmi; Ghosh, Arghya; Joseph, Sumi; Reddy, Santhi Vardhan; Biju, Akkattu T. (Chemical Communications, 2017)
A mild, general, and high yielding synthesis of N-acyl 2-aminobenzothiazoles has been demonstrated by N-heterocyclic carbene (NHC)-organocatalyzed direct amidation of aldehydes with 2-aminobenzothiazoles proceeding via acyl azolium intermediates. The carbene generated from the triazolium salt under oxidative conditions was the key for the success of this reaction. The method was subsequently applied to the synthesis of various biologically important N-acyl 2-aminobenzothiazoles.